Plastisphere - a new habitat of microbial community: Composition, structure and ecological consequences - Lavanya Mulky; Jithu George Valiaparampil; Divyashree Somashekara (Sustainable Environment)
The pervasive accumulation of non-degradable plastics has escalated ecological threats to the environment. These materials exhibit a strong affinity for microplastics (MPs), which serve as carriers for hazardous chemicals and pathogens, ultimately leading to the formation of plastispheres. Microplastic (MP) pollution is now widespread across multiple biomes, where they host microbial communities that form biofilms with diverse compositions and functions. MPs provide microhabitats for microbes in marine and terrestrial environments, creating unique microenvironments as these organisms colonize plastic surfaces. This study explores the emergence of plastispheres—microbial biofilms that develop on microplastics in marine and terrestrial environments. It highlights how MPs act as vectors for harmful pollutants and pathogens, fostering unique microbial communities with ecological implications. The review analyzes the composition, structure and functional dynamics of plastispheres, alongside the environmental factors driving their formation. This review examines the community composition, structure and function of plastispheres, while also evaluating the factors influencing biofilm formation and the potential ecological risks posed by these synthetic ecosystems. Finally, it assesses the ecological risks associated with these plastic-bound ecosystems, emphasizing their role in global pollution and ecosystem disruption.